Needs and ways to meet them by adolescents during adolescence - Kuszniar, Klaudia; Firlej, Ewelina; Janiszewska, Mariola; Konarska, Jagoda; Kustra, Paulina; Barańska, Agnieszka (Journal of Education, Health and Sport, 2017)
Introduction. The needs of man derive from his biological and psychological conditioning. Each unit, due to its individuality, generates different needs. Especially in adolescence, a person feels more strongly about his or her own desires. The drive of life leads him towards adulthood and independence from parents. This causes the desire to get to know the world, people and experiment. Young people are characterized by impulsiveness; quick and ill-considered decisions and risky behaviors. Target. The aim of the work was to show the needs and ways of satisfying them by youth in adolescence. Summary. The needs of man are varied as well as the ways of satisfying them. Satisfaction of needs is extremely important in the proper functioning of man. Unmet needs have a negative impact on the daily functioning of the individual. In a situation in which young people are unable to cope with a sense of lack, they are subconsciously motivated to fill emptiness. Building the hierarchy of needs for each person takes on a different form, because what people lack depends on their level of intelligence, education, life experiences, environment, family and material situation. It is important to conduct research on the needs of adolescents and how they can be met during adolescence in order to best support young people in achieving their own adult goals.